Impact of guideline changes on adoption of hypofractionation and breast cancer patient characteristics in the randomized controlled HYPOSIB trial - Krug, David; Vonthein, Reinhard; Schreiber, Andreas; Boicev, Alexander D.; Zimmer, Jörg; Laubach, Reinhold; Weidner, Nicola; Dinges, Stefan; Hipp, Matthias; Schneider, Ralf; Weinstrauch, Evelyn; Martin, Thomas; et al. (Strahlentherapie und Onkologie, 2021)
Hypofractionated radiotherapy is the standard of care for adjuvant whole breast radiotherapy (RT). However, adoption has been slow. The indication for regional nodal irradiation has been expanded to include patients with 0-3 involved lymph nodes. We investigated the impact of the publication of the updated German S3 guidelines in 2017 on adoption of hypofractionation and enrollment of patients with lymph node involvement within a randomized controlled phase III trial.
Online veröffentlicht: 15 Dezember 2020
Gesehen am 7.11.2023